Human Milk Microbiota Profile Affected by Prematurity in Argentinian Lactating Women - Oddi Sofia; Mantziari Anastasia; Huber Paula; Binetti Ana; Salminen Seppo; Collado Maria Carmen; Vinderola Gabriel (MDPI, 2025)
To study (16S rRNA-sequencing) the impact of gestational and corrected ages on the microbiota profile of human milk (HM) of mothers that delivered full-term and pre-term children, HM samples were obtained and classified according to the gestational age as group T (full-term births >= 37 weeks), and group P (pre-term births <37 weeks). Group P was longitudinally followed, and the samples were collected at the full-term corrected gestational age: when the chronological age plus the gestational age were >= 37 weeks (PT group). The HM microbiota composition differed depending on the gestational age (T vs. P). Group T had lower levels of Staphylococcus and higher levels of Rothia and Streptococcus, as compared to group P. The alpha Simpson diversity value was higher in group T than in P, whereas no differences were found between groups T and PT, suggesting a microbial evolution of the composition of group P towards group T over chronological age. Full-term delivery was associated with a greater diversity of microbes in HM. The microbial composition of pre-term HM, at the corrected age, did not show significant differences, as compared to the samples obtained from the full-term group, suggesting that it would be appropriate to consider the corrected age in terms of the composition and the diversity of the milk in future studies.